2016
DOI: 10.1097/cji.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Melanoma-reactive CD4+ T-Cell Subsets From Human Melanoma Draining Lymph Nodes

Abstract: Our laboratory has previously demonstrated that melanoma draining lymph node (MDLN) samples from stage III patients contained both CD4+ and CD8+ T cells that can be readily expanded to mediate tumor cell apoptosis in vitro and improve survival in mice bearing human melanoma xenografts. In this study, we investigated whether MDLN T cells contain melanoma-reactive CD4+ T cell compartment and what they are. In order to test this, we performed multi-parametric (11-color and 6-color) FACS analyses to monitor phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As part of the T cell characterization in this report, CD8B and CXCR5 were shown to mark a subset of memory CD4 T cells, which specialize in supporting antibody-mediated immune responses ( Chevalier, et al, 2011 ). Furthermore, a multi-parametric FACS analysis of melanoma-reactive CD4 T cells from stage III malignant melanoma patients revealed elevated CXCR5 expression in a subset of CD4 T cells with enhanced responsiveness to melanoma cell antigen reexposure ( Zhang et al, 2016 ). In addition to its role as a receptor for T cell priming and B cell activation ( Elgueta, et al, 2009 ), functional expression of CD40 was shown in a recent study by Levin et al (2018 ) to increase IFN-γ secretion and improve the functional properties of human CD8 cells, CD4 cells, and a subset of TILs in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the T cell characterization in this report, CD8B and CXCR5 were shown to mark a subset of memory CD4 T cells, which specialize in supporting antibody-mediated immune responses ( Chevalier, et al, 2011 ). Furthermore, a multi-parametric FACS analysis of melanoma-reactive CD4 T cells from stage III malignant melanoma patients revealed elevated CXCR5 expression in a subset of CD4 T cells with enhanced responsiveness to melanoma cell antigen reexposure ( Zhang et al, 2016 ). In addition to its role as a receptor for T cell priming and B cell activation ( Elgueta, et al, 2009 ), functional expression of CD40 was shown in a recent study by Levin et al (2018 ) to increase IFN-γ secretion and improve the functional properties of human CD8 cells, CD4 cells, and a subset of TILs in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The TdLN-derived T-cell culture and expansion was conducted based on our published protocols [ 18 , 19 , 20 ]. Briefly, one million B16F10 cells were subcutaneously injected into the flanks of donor WT C57BL/6J mice on day 0.…”
Section: Methodsmentioning
confidence: 99%